The Multidimensional Role of Family Members in Dietary Supervision for Hypertension Patients: A Descriptive Phenomenological Study - Wirda Faswita; Eqlima Elfira (Caring: Indonesian Journal of Nursing Science, 2026)
Long-term dietary regulation, characterized by the reduction of sodium and fat intake along with increased fiber consumption, serves as a crucial non-pharmacological component for controlling blood pressure in patients with hypertension. Therefore, this study aims to identify and analyze the various dimensions of the family's role in dietary supervision for members suffering from hypertension. The study procedures were carried out at UPT Puskesmas Medan Sunggal (July-August 2025) using a qualitative design with a descriptive phenomenology approach. The participants (n=8) were selected using a purposive sampling method. Data from semi-structured interviews were analyzed using Colaizzi’s seven-step method, involving transcription, significant statement extraction, and thematic formulation. The results showed that the family's role was divided into 3 interconnected main categories. First, the family as a practical supervisor and food environment modifier, where members actively limited the use of salt, oil, and flavor enhancers during cooking and controlled the availability of fast food at home. Second, the family as motivation and emotional coping supporter, where members provided encouragement, reminded the patient using gentle language, and helped the patient cope with the frustration associated with dietary changes. Third, as a behavior model and informal educator, where members collectively adopted healthier eating patterns (low salt), preventing the patient from feeling isolated, and proactively provided nutritional information. These results recommend the empowerment of families by the primary health center to improve communication skills and the preparation of healthy meals that are acceptable to hypertensive patients. Keyword: Dietary Supervision, Family Members, Hypertension, Role